Effect of Crushed Glass Cullet Sizes on Physical and Mechanical Properties of Red Clay Bricks - Patricia Ponce Peña; María Azucena González Lozano; Alicia Rodríguez Pulido; René Homero Lara Castro; Zoe V. Quiñones Jurado; Juan Carlos Pérez Medina; Martha Emilia Poisot Vázquez; Axel Villavicencio Torres (Advances in Materials Science and Engineering)
This study reports the effect of clear waste glass from bottles added on 20 to 30 wt.% and variable particle size (<500, <300, and <212 μm), into clay mixtures for the handmade brick manufacturing process. The bricks were manufactured with mixtures of clay, crushed glass, and water in different proportions, homogenized, casted in wooden molds, air-dried at room temperature for 72 h, and sintered at 1000°C for 12 h. Total shrinkage, water absorption, compressive strength, microstructure, and phase composition are discussed with respect to glass content and its particle size. The results indicate that increasing the content of glass and decreasing its particle size enhanced significantly the brick properties of water absorption and compressive strength by up to 18.5% and 6.8 MPa, for bricks with 30 wt% and particle size lower than 212 μm. It is proposed that decreasing the glass particle size its surface area increases allowing easier melting of glass by lower energy consumption, reducing porosity and enhancing brick properties.